1989
DOI: 10.1002/jnr.490230304
|View full text |Cite
|
Sign up to set email alerts
|

Complete sequence of a cDNA encoding an active rat choline acetyltransferase: A tool to investigate the plasticity of cholinergic phenotype expression

Abstract: A cDNA clone encoding the complete sequence of an active rat choline acetyltransferase (ChoAcTase; acetyl-CoA:choline O-acetyltransferase, EC 2.3.1.6) has been isolated. Analysis of the deduced amino acid sequence reveals 85% and 31% identity with the porcine and Drosophila melanogaster enzymes, respectively. To further elucidate the molecular basis of neurotransmitter-related phenotypic plasticity, the expression of ChoAcTase mRNA was compared with that of tyrosine hydroxylase [TH; tyrosine 3-monooxygenase, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(104 citation statements)
references
References 28 publications
1
102
0
1
Order By: Relevance
“…The ChAT mRNA (Brice et al, 1989) was identified using a pair of primers flanking a splicing site near the 3' terminus of the coding region. The upper primer was 5'-ATG GCC ATT GAC AAC CAT CTT CTG (nucleotides 1729-1752) and located on exon 14.…”
Section: Methodsmentioning
confidence: 99%
“…The ChAT mRNA (Brice et al, 1989) was identified using a pair of primers flanking a splicing site near the 3' terminus of the coding region. The upper primer was 5'-ATG GCC ATT GAC AAC CAT CTT CTG (nucleotides 1729-1752) and located on exon 14.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis of 100 ng rat b-amyloid(1-42) showed a strong single band of 4 kDa and a weaker band at 12 kDa under reducing or non-reducing conditions. Western blot analysis of 100 ng sbAPP protein showed a strong band of approximately 100 kDa under non-reducing conditions with the anti-APP A4 antibody, whereas no sbAPP-protein (1000 ng) was detectable with the anti-b-amyloid (17)(18)(19)(20)(21)(22)(23)(24) antibody. Brain slices incubated for 12 or 16 weeks at physiological pH tested conditions (pH 7.2 or pH 6.0, 7ApoE4, 2 weeks 371C) when the mix was loaded directly onto the gel.…”
Section: Effects Of Acidosis On Brain Slicesmentioning
confidence: 94%
“…18 Briefly, brain slices were transferred onto slides (ProbeOn slides, Fisher Biotech, Pittsburgh, PA, USA) and frozen in a CO 2 stream and stored at À201C until use. Antisense oligonucleotides complementary to nucleotide base pairs 1818-1860 of the choline acyteltransferase (ChAT) gene (43mer) 19 and the APP695 gene (40mer) 20 were labeled at the 3 0 end with [a- 35 S]dATP using terminal deoxyribonucleotidyl transferase (New England Nuclear, Vienna, Austria) and purified using Qiagen nucleotide removal kit (Qiagen, Vienna, Austria). Sections were hybridized at 421C overnight in a humidified chamber with 0.1 ml per slide of a hybridization solution (50% formamide, 4 Â SSC, 0.02% polyvinylpyrrolidone, 0.02% Ficoll, 0.02% bovine serum albumin, 10% dextran sulfate, 0.5 mg/ml sheared salmon sperm DNA, 1% sarcosyl (N-lauroyl sarcosine), 0.02 M NaPO4 (pH 7.0), 50 mM dithiothreitol) containing 1 Â 10 7 c.p.m./ml probe.…”
Section: Postmortem Alzheimer Brainmentioning
confidence: 99%
See 2 more Smart Citations